The relationship between meteorological factors and mumps incidence in Guangzhou, China, 2005–2012:: A distributed lag nonlinear time-series analysis - Yang, Qiongying (Hum Vaccin Immunother, 2014)
Background Over the past decade, there have been resurgences and large-scale outbreaks of mumps worldwide. Little evidence is available on the relationship between meteorological factors and the incidence of mumps. We aimed to explore the effects of meteorological factors on mumps incidence. Methods: A Poisson regression model combined with a distributed lag non-linear model (DLNM) was used to evaluate the association between meteorological factors and the mumps incidence in Guangzhou, China, 2005–2012. Results Nonlinear relationships between meteorological factors, except sunshine hours, and mumps incidence were observed. The relative risks (RRs) of mean temperature, relative humidity and atmospheric pressure were 1.81 (95% confidence interval (CI), 1.41 to 2.32), 1.28 (95% CI, 1.02 to 1.59), and 0.80 (95% CI, 0.67 to 0.95) comparing the 99th percentile to the median of their own, respectively. For wind velocity, the RR was 0.70 (95%CI, 0.54 to 0.91) comparing the 1st percentile to the median. The hot effect and cold effect were larger in females than in males, and the hot effect increased with age. Conclusions Mean temperature, relative humidity, wind velocity and atmospheric pressure might be important predictors of the mumps incidence. Tropical cyclone caused a higher increase in mumps cases. Our findings highlight the need to strengthen the awareness of using protective measures during typhoon days and allocating more attention to the susceptible populations during the summer. The two-dose regimen of mumps vaccine should be included in the National Immunization Program schedule, and the catch-up vaccination campaigns should be promoted among adults.